Sediment Granulometry of the Beach at the Kalasey’s Groynes - Simboh, Reyvalentin; Rampengan, Royke M; Manengkey, Hermanto W.K.; Djamaluddin, Rignolda; Opa, Esry T; Sinyal, Hengky J (Jurnal Ilmiah Platax, 2021)
Coastal areas have the potential to be developed and utilized for various purposes. However, the intensity of coastal use can result in the degradation of the coastal environment. Therefore, management of the coastal areas is often carried out by building shore protective structures, including groynes. The placement of a structure in the form of a groynes is primarily intended to block littoral flow in moving sediment out of certain places in the shore. Therefore, the placement of groynes on the shore needs to be followed by a study to find out the effectiveness of the groynes. The effectiveness of groynes can be determined, among others, by a study on the granulometry of sediments on the beach. This study was conducted to describe the composition of the sediment and to analyze granulometry distribution in several places at the beach around the groynes on the shore of Kalasey. The study of the physical sediments around the Kalasey groynes was carried out through a study of the sediment samples from October 30, 2020, to April 27, 2021. Sediment sampling was carried out at 6 stations which have been determined on the surface of the beach formed around the groynes. The results obtained through this research showed that the composition of the sediments in the beach around the Kalasey groynes consisted of size classes as follows: very fine sand, fine sand, medium sand, coarse sand, very coarse sand, granule, and pebble. Fine-sized materials at the beach which is located in the groynes on further east have increased in composition. Based on the granulometric analysis of the sediment, it is indicated that the erosion and deposition processes occur alternately in the beaches formed around the groynes.Keywords: Beach; Kalasey Groynes; Sediment Composition; Granulometric AnalysisAbstrakWilayah pantai memiliki potensi untuk dikembangkan dan dimanfaatkan untuk berbagai kepentingan.  Walaupun demikian, intensivitas pemanfaatan pantai dapat mengakibatkan terjadinya degradasi lingkungan pantai.  Oleh karena itu, dalam rangka pengelolaan pantai seringkali dilakukan dengan cara membangun struktur pelindung pantai, diantaranya berupa groin. Penempatan struktur berupa groin di kawasan pantai, dimaksudkan utamanya untuk menghadang aliran litoral dalam memindahkan sedimen keluar dari tempat tertentu di kawasan pantai.  Oleh karena itu, penempatan groin di pantai perlu diikuti dengan kajian untuk melihat efektivitas fungsi groin pada kawasan pantai tersebut.  Salah satu cara untuk melihat efektivitas kerja groin di pantai adalah melalui kajian menyangkut granulometri sedimen gisik yang terhampar di sekitar groin yang ditempatkan. Penelitian ini dilakukan dengan tujuan mendeskripsikan komposisi sedimen dan menganalisis distribusi granulometri di beberapa tempat pada gisik sekitar groin di pantai Kalasey.  Kajian terhadap sedimen gisik sekitar groin Kalasey dilakukan melalui telaah terhadap sampel sedimen yang dicuplik mulai 30 Oktober 2020 sampai dengan 27 April 2021.  Pencuplikan sedimen dilaksanakan di 6 stasiun yang ditetapkan pada permukaan gisik yang terbentuk di sekitar groin Kalasey. Hasil yang diperoleh melalui penelitian ini adalah komposisi sedimen pada gisik di sekitar groin Kalasey terdiri dari kelas ukuran berupa pasir sangat halus, pasir halus, pasir sedang, pasir kasar, pasir sangat kasar, granul, dan kerakal.  Gisik yang terletak pada kawasan groin semakin ke arah Timur pada kawasan ini, komposisi sedimennya mengalami peningkatan jumlah material sedimen yang berukuran halus.  Berdasarkan analisis granulometri sedimen terindikasi bahwa proses erosi dan deposisi terjadi secara bergantian pada gisik-gisik yang terbentuk di sekitar groin.Kata kunci: Gisik; Groin Kalasey; Komposisi Sedimen; Analisis Granulometri